Assessment of Marine Water Quality in Quang Binh and Quang Ngai Provinces for Tourism Development Activities - Phong, Nguyen Hai; Hai, Truong Quang; Tuan, Nguyen Quang; Vu, Ho Xuan Anh (VNU Journal of Science: Earth and Environmental Sciences, 2020)
This article assessing status of water quality in coastal areas of Quang Binh and Quang Ngai provinces for the purpose of tourism development. The results of research showed that water quality at monitoring sites at the beaches in Quang Binh and Quang Ngai provinces met requirements of QCVN 10-MT:2015/BTNMT for beach and underwater sport. Particularly with parameters such as: turbidity (NTU) at LS2, LS7 and LS14 sites exceed standards of ASEAN and chemical oxygen demand (COD) was increased. However, COD is not regulations in QCVN 10-MT: 2015 / BTNMT, ASEAN and Australia but when compared with QCVN 01: 2009 / BYT are more than two times. This can influence for health when exposed to coastal water in tourist areas.